Career management - Forsyth, Patrick (ExpressExec life & work, 2002)
Covers key career management techniques, from lifelong learning to getting promoted, and from surviving office politics to goal setting. This book includes a glossary of key concepts and a comprehensive resources guide. It is suitable for people who need to master business thinking and practice quickly.